Pan American climate resilient health systems: a training course for health professionals - Cecilia Sorensen; Carolos Barboza; Peter Berry; Daniel Buss; Haley Campbell; Kristie Hadley; Nicola Hamacher; Danielly Magalhaes; Gilma Mantilla; Anwar Mendez; Karen Polson-Edwards; Anna Stewart-Ibarra; et al. (Pan American Health Organization, 2024)
Objectives To describe the development, implementation, and results of a training course designed to equip health professionals from the Pan American Health Organization region with the knowledge and tools needed to adapt health systems to current climate realities Methods The Pan American climate resilient health systems course was a 9-week live-virtual course in MarchApril 2023, which was delivered through Zoom and offered in English, Spanish, and French. All lectures were delivered by local and regional climate and health experts. The curricular foundation of this initiative was the Global Consortium on Climate and Health Education core competencies for health professionals. Participants completed pre- and post-course surveys Results A total of 1212 participants attended at least one of the nine sessions and 489 (from 66 countries) attended at least six sessions. Of these, 291 participants completed both the pre- and post-course surveys which were used in the analysis. Longitudinal survey results suggested an improvement in participants climate and health communication, an increased frequency of incorporating climate knowledge in professional practice, and improved confidence in engaging in climate initiatives. At the same time, many participants expressed a need for additional training Conclusions The results indicate that live-virtual courses have the potential to empower health professionals to contribute to climate resilience efforts by: increasing their communication skills; changing their professional practice; increasing their ability to lead climate and health activities; and preparing them to assess vulnerability and adaptation in health systems, measure and monitor environmental sustainability, and apply a health equity lens.